Field performance and bioactive content of in-vitro derived aloe vera (Aloe vera l. burm. f.) as influenced by planting distance, fertilization and plant material - Sarmiento, Jose Arnel T. (Journal of ISSAAS, 2020)
Four (4) sets of Aloe vera plantlets propagated in-vitro and acclimatized in four potting media – designated as planting material types (PM) – were cultivated in open field to evaluate growth, yield and bioactive content and subjected to three (3) planting distances (PD) and three (3) fertilizer types (F). The four potting media were PM1-in garden soil (GS), PM2-in garden soil and sand medium (GS:S) 1:1 v/v, PM3-in garden soil and carbonized rice hulls (GS:CRH) 1:1 v/v and PM4-in garden soil and coco peat (GS:CP) 1:1 v/v. Fresh weight and volume of leaves of mother plant in the 10th (last) month were affected by PD. All planting material treatment combinations used except PM1, PM2, PM3 and PM4 significantly differed in harvested volume of peel. GS-CP (PM4) and GS-CRH (PM3) hardened propagules significantly increased the volume of gel against GS (PM1). At 60cm x 45cm, %N in leaves was highest but comparable %N at 60cm x 30cm while %P in leaves was significantly higher with chicken manure urea-solophosmuriate of potash. %P in leaves was higher in plants acclimatized in GS-CRH compared to plants acclimatized in GS-CP. ppm K in leaves at 60cm x 30cm spacing was significantly higher than at 60cm x 60cm. Aloin A in leaves was significantly higher with complete fertilizer than with chicken manure-urea-solophos-muriate of potash. Aloe emodin production of plants acclimatized in GS-S differed significantly between plants spaced at 60x45 cm and 60x30 cm, and between plants applied with complete fertilizer against chicken manure-urea-solophos-muriate of potash. Aloe emodin per unit area varied significantly between GS and GS-S at 60x30 cm.